THE ISLAMIC VALUES OF MYSTICAL REASON IN "KEBO-KEBOAN" TRADITION IN BANYUWANGI - Puput Lestari; Khoirul Hadi Al Asy’ari (Islamuna: Jurnal Studi Islam, 2023)
ABSTRACT One of the diversity of Indonesian manners and cultures is the Osing tribe lived in most Banyuwangi area. This tribe has an interesting traditional ritual, namely the "Kebo-keboan". The Osing tribe believe that this tradition is a heritage that must be perpetuated. The mystical dimension is often displayed by the Osing in this ritual. This study is interesting for it examines Islamic values ​​in the mysticism of the "Kebo-keboan" tradition in Banyuwangi district. There are three important questions in this study, 1) how is the ritual tradition of "Kebo-keboan" in Banyuwangi take place along with its practice and implementation?, 2) how does the Osing tribe understand the ritual of "Kebo-keboan"? and 3) what are the Islamic values ​​in the mystical of the "Kebo-keboan" tradition in Banyuwangi? In this study the method uses qualitative and descriptive analysis. the results of this study is expected to contribute toward Islamic studies in culture of society, especially those related to the ritual traditions of "Kebo-keboan" in Banyuwangi. ABSTRAK Salah satu keragaman adat dan budaya Indonesia yakni ada pada suku Osing yang mendiami sebagian besar wilayah Banyuwangi. Suku ini memiliki ritual adat yang menarik yaitu ritual adat “Kebo-keboan”. Masyarakat Osing meyakini bahwa ini adalah warisan adat leluhur yang harus di lestarikan. Dimensi mistis sering ditampakkan oleh masyarakat adat Osing dalam ritual ini. Penelitian ini menjadi menarik diangkat karena mengkaji nilai-nilai Islam dalam nalar mistisisme tradisi “Kebo-keboan” di kabupaten Banyuwangi. Ada tiga pertanyaan penting dalam penelitian ini, 1) bagaimana tradisi ritual adat “Kebo-keboan” di kabupaten Banyuwangi berlangsung dan bagaimana sejarah praktek dan implementasinya? 2) bagaimana pemahaman masyarakat Osing Banyuwangi terhadap ritual adat “Kebo-keboan”? dan 3) bagaimana nilai-nilai Islam dalam nalar mistisisme tradisi “Kebo-keboan” di kabupaten Banyuwangi? Metode penelitian ini menggunakan kualitatif dan analisis diskriftif. Hasil penelitian ini diharapkan akan memberikan sumbangsih tantang studi keislaman dalam budaya masyarakat, khususnya terkait dengan tradisi ritual adat “Kebo-keboan” di kabupaten Banyuwangi.